Comparison of Acute Level of CK After Five Weeks Eccentric vs Concentric High Intensity Strength Exercise in Healthy Subject - Hasni Hasni; Hening Laswati Putra; Nuniek Nugraheni (Faculty of Medicine, Universitas Airlangga, 2019)
Background: Musculoskeletal injuries both in sport and recreational activities, at each age level, can lead to immobilization. Injury and immobilization can lead to muscle strength decrease and deconditioning. These conditions can be addressed by provision of strength training therapy especially for people with low exercise tolerance such as the elderly and patients with chronic disease. Existing studies stated eccentric exercise can increase muscle strength with less energy expenditure compared to concentric exercise. However eccentric exercise can lead to muscle damage indicated with an acute CK level increase, and eccentric exercise has not been carried out regularly for post muscle injuries and deconditioned patients. The American College of Sport Medicine (ACSM) stated strength increase and muscle hypertrophy require high intensity load strengthening exercise with a minimum load of 70% 1 Maximum Repetition. The recommended load was given to the subjects in this research. Our pleriminary study intervention was well tolerated by healthy subjects.Aim: Comparing acute CK level alteration in high intensity eccentric and concentric muscle strengthening exercise on untrained healthy subjects.Methods: Randomized pre test and post test group design. Subjects of the study (n = 16) were untrained healthy males. CK level was evaluated by laboratory test.Results: Our study showed decline of acute CK level in both groups with p value 0.65 and 0.76, respectively. No significant differences found on both groups.Conclusion: The increase of acute CK level after five weeks of eccentric strengthening exercise is not higher than that in concentric strengthening exercise.